Peran Vegetasi Penutup Tanah Dalam Menekan Laju Erosi Dan Meningkatkan Infiltrasi Air - Lilis Sartika Gulo; Natalia Kristiani Lase (Jurnal Ilmu Pertanian dan Perikanan, 2025)
This study aims to analyze the role of vegetative ground cover in reducing erosion rates and increasing water infiltration on sloped lands. The method employed was a field experiment with three treatments: bare land without cover, land planted with vetiver grass, and land planted with leguminous cover crops. The results indicate that vegetative ground cover significantly reduced erosion rates by up to 65% and increased water infiltration rates to more than twice that of bare land. Vetiver grass was found to be more effective than legumes in strengthening soil structure and improving soil physical properties. These findings highlight the importance of utilizing vegetative ground cover as a conservation strategy to maintain soil productivity and preserve water resources. The implementation of vegetative cover is highly recommended for sustainable land management, especially in erosion-prone areas.